Collaborative Mentoring as a Way of Meeting Teachers' Inclusive Teaching Practices Needs: Investigating Learning Outcomes - Kamalı-Arslantaş Tuğba; Yalçın Gülistan (Sciendo, 2023)
Introduction: This article discusses a mentoring project that was aimed at improving the inclusive education practices of teachers.